2000
DOI: 10.1007/bf02390538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of asthma on the quality of life among children and their caregivers in the Atlanta empowerment zone

Abstract: Background and Objective. Asthma is the most common chronic pediatric disease and exacts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
4
21
0
1
Order By: Relevance
“…The leading factor for deterioration of quality of life is severity of asthma. Severe asthma suggests lower level of quality of life for parents as caregivers [15,17,28].…”
Section: Discussionmentioning
confidence: 99%
“…The leading factor for deterioration of quality of life is severity of asthma. Severe asthma suggests lower level of quality of life for parents as caregivers [15,17,28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have either shown a positive association (Kub et al, 2009), or did not find any significant association in a sample of low income mothers (Shalowitz et al, 2006). Other research focused more extensively on the impact of child asthma on parents' quality of life (Levy et al, 2004;Williams et al, 2000;Ozkaya et al, 2010;Wright, 2011) or on the impact of maternal depression on child asthma morbidity and use of health care services (Bartlett et al, 2001;Klinnert et al, 2001). Defining and diagnosing child asthma is particularly difficult during the first years of life as asthma-like symptoms are unstable and can be due to other ailments (Klinnert et al, 2001;Kurukulaaratchy, Matthews, & Arshad, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Mothers of children with allergic diseases are more anxious, psychologically unstable, overprotective, and often demonstrate negative emotions toward their children 5,6. There are significant correlations between a caregiver's quality of life and the severity of children's allergic symptoms and with the quality of life of the child 7,8…”
Section: Introductionmentioning
confidence: 99%